FLOWS AND FUNCTIONS: AN EXPERIENCE REPORT ON USERS’ PERCEPTIONS OF THE FHS IN A PHU IN EUNÁPOLIS, BAHIA - Almeida da Silva, Flaelma; Ivny Lima Silva, Brenda; Ivina Lima Silva, Bárbara; de Lima, Diana; Santana dos Santos, Tatiana (Health and Society, 2025)
This article presents an academic experience developed within a university extension project linked to the Medicine program at Faculdade Pitágoras de Eunápolis. The study adopts a perceptual approach focused on analyzing users’ opinions regarding the service flow and the functions performed by the multidisciplinary team of the Family Health Strategy (FHS) at the São João Batista Basic Health Unit. Structured instruments were used for data collection, based on a questionnaire composed of nineteen closed-ended questions applied to a sample of thirteen users. The results showed that 61.5% rated the service as “regular” and 38.5% as “good” or “excellent”, with no negative responses recorded. Regarding professional listening, 46.1% stated they are “always listened to” and 38.5% reported being listened to “sometimes”, indicating positive but inconsistent communication practices. As for the team’s knowledge of community health conditions, 69.2% demonstrated a positive perception, while 30.8% identified some degree of unawareness. The main challenges to accessing the unit were long waiting lines (53.8%) and lack of information (23.1%). The most frequently mentioned improvement suggestions included enhancing the physical infrastructure of the unit, followed by increasing the number of professionals and improving communication with patients. The experience adhered to the ethical principles required for research involving human subjects, with all participants signing an Informed Consent Form and formal authorization obtained from the Eunápolis Municipal Health Department for the implementation of the activity. It is concluded that strengthening active listening and integrating teaching, service, and community represent essential paths to improving primary health care and enhancing the transformative effects of university extension.